Four new species of Cortinariaceae (Agaricales) from Northwestern China - Fan, Longfei; Zhong, Xue; Ma, Tianfu; Zhou, Hongmin; Wang, Biyue; Ji, Xiaohong (Frontiers in Microbiology, 2024)
Cortinariaceae, belonging to the Agaricales, is a worldwide family known for its high species diversity. Eight ITS and nLSU sequences were newly generated, and phylogenetic analyses were performed by the combined ITS and nLSU datasets. The four species formed four independent lineages with robust support in phylogenies based on both datasets. Four new species in the taxa, Cortinarius gansuensis, Cortinarius tricholomoidus, Cortinarius vinoso-griseum, and Phlegmacium subcalyptratum are described and illustrated from northwestern China based on morphological and molecular evidence. Cortinarius gansuensis is characterized by convex and brownish vinaceous pileus, generative hyphae with clamp connections, ellipsoid basidiospores (8.5-10.6 × 5.4-6.8 μm); Cortinarius tricholomoidus is characterized by broadly umbonate and snuff brown pileus, generative hyphae with clamp connections, broadly ellipsoid to subglobose basidiospores (7.4-8.5 × 6.2-7.3 μm); Cortinarius vinoso-griseum is characterized by the violaceous grey pileus, generative hyphae with clamp connections, smaller basidiospores (7.5-9.7 × 5.6-7.8 μm); Phlegmacium subcalyptratum is characterized by small and apricot-orange pileus, generative hyphae with clamp connections, fusiform basidiospores (10.0-12.7 × 5.6-6.8 μm). Full descriptions, illustrations and phylogenetic analysis results of the four species and discussions with related species are provided.